Assessment of Patients Misunderstanding of Dosing Instructions Among Outpatients in Dessie Referral Hospital, Northeast Ethiopia - Mengesha Y; Amare E (Dove Medical Press, 2020)
Yohannes Mengesha, Eskedar Amare Department of Pharmacy, College of Medicine and Health Sciences, Wollo University, Dessie, EthiopiaCorrespondence: Yohannes Mengesha Email joymengesha@gmail.comBackground: Lack of clear and precise oral and written information from both the doctors and/or pharmacists on the management of prescribed medication has led to therapeutic failure, as a result of patients not comprehending instructions. Incorrect interpretation of labels can lead to incorrect usage of medication therefore the occurrence of medication error and/or adverse event. The concern of this study was to assess misunderstanding of dosing instructions among outpatients in Dessie Referral Hospital (DRH).Methods: An institution-based cross-sectional study was conducted on 384 outpatients at DRH from February 10 to March 15, 2019. Study subjects were selected by using a systematic random sampling technique and data was collected by using questionnaires and observation. The data was coded individually and entered in a computer using Epi Info™ version 3.5.1 and then exported to SPSS version 23.0 for analysis. Univariate analyses were used to describe the categorical variables. Chi-square test was used to assess association of variables with primary outcome. P-value < 0.05 was considered as statistical significance.Results: This study showed that most of the respondents n=298 (77.6%) misunderstood more than one dosage instruction, 8.75% misunderstood the dose, 51.3% misunderstood the frequency while 58.59% misunderstood the duration of treatment. The misunderstanding was higher for labeled medications (11.4%) than unlabelled (7.7%).Conclusion: The prevalence of misunderstanding of dosing instruction was high in outpatients of DRH. Hence standard procedures must be developed to provide easy and clear dosing instructions to patients, and continuous training must be provided for pharmacists on proper communication of dosing instructions to patients.Keywords: dosing instruction, DRH, outpatients